Level of optimal antenatal care utilization and its associated factors among pregnant women in Arba Minch town, southern Ethiopia: new WHO-recommended ANC 8+ model - Deresa Dinagde, Dagne; Feyisa, Gizu Tola; Afework, Hana Tadesse; Chewaka, Menen Tilahun; Wada, Habtamu Wana (Frontiers in Global Women's Health, 2024)
To fully realize the life-saving and health-promoting benefits of antenatal care, the latest WHO recommendations call for pregnant women to have at least 8 contacts with skilled healthcare providers. This increased number of recommended ANC visits represents a shift towards a more comprehensive, individualiz the key risk factors that prevent adequate antenatal care would have significant implications for increasing overall ANC uptake in these regions.To gain the life-saving and health-promoting promises of antenatal care, pregnant women need to have at least eight contacts with skilled healthcare providers, yet coverage in Sub-Saharan African countries, including Ethiopia, is only 58%. H adequate antenatal care would have reasonable implications for increasing antenatal utilization.Objective: To assess the level of optimal antenatal Care utilization and its Associated Factors among Pregnant Women in Arba Minch Town: southern Ethiopia in 2023: WHO New recommendation ANC 8+ model.An institution-based cross-sectional study was conducted among 416 mothers who were enrolled from December 1, 2022, to January 30; 2023. The total sample size was allocated proportionately to the number of women who delivered at each public health facility. Thus, systematic sampling was applied. Kobo Toolbox was used for data collection and cleaning, which was then analyzed using SPSS Version 26. Statistical significance was determined at a p-Value of less than 0.05.In this study the level of optimal antenatal care was 41% at a (95% CI: 37-45.3). The associated factors with optimal antenatal care were presence of pregnancy danger signs (AOR = 4.1, 95CI:1.87, 8.82), having bad obstetric history (AOR=3.90, 95CI:1.94,7.83), antenatal contact at hospital (AOR=5.1, 95CI:2.28,11.21), having good knowledge about antenatal care (AOR =2.26, 95%CI:1.15,4.44), women's low high decision making power (AOR=3.9, 95CI:1.2,7.63) and , male partner involvement (AOR=2.0, 95CI: 1.04,3.78) were positively associated with optimal antenatal care utilization.Conclusion: the level of optimal antenatal follow up is still low. Therefore, it's crucial to provide more information during the antenatal contacts in order to lower the rate of women discontinued from antenatal care.